Downregulation of CD163 in monocytes and its soluble form in the plasma is associated with a pro-inflammatory profile in pregnant women with preeclampsia - Nunes, Priscila R. [UNESP]; Romão-Veiga, Mariana [UNESP]; Peraçoli, José C. [UNESP]; Araujo Costa, Roberto A. [UNESP]; de Oliveira, Leandro G. [UNESP]; Borges, Vera Therezinha M. [UNESP]; Peraçoli, Maria Terezinha [UNESP] (Springer Nature, 2019)
Preeclampsia (PE) is a pregnancy-specific syndrome characterized by a systemic inflammatory response that polarizes peripheral blood monocytes to the M1 phenotype. The classically activated M1 monocytes comprise immune effector cells with an acute inflammatory phenotype. CD163 is a scavenger receptor expressed by monocytes/macrophages that may be shed from their cell membrane after proteolytic cleavage, producing the soluble CD163 molecule (sCD163). This study evaluated CD163 expression by monocytes and sCD163 as well as pro- and anti-inflammatory cytokine concentration in the plasma of pregnant women with PE. Fifty-six women with PE and 28 normotensive pregnant women were included. Plasma levels of sCD163, interleukin-1 beta (IL-1β), IL-6, IL-10, transforming growth factor beta (TGF-β1), and tumor necrosis factor-alpha (TNF-α) were determined by ELISA, and CD163 expression by monocytes was assessed by flow cytometry. The expression of CD163 by monocytes was significantly lower in severe and mild PE than in normotensive pregnant. Plasma concentrations of IL-1β, TGF-β1, and TNF-α were higher in severe PE than in mild PE and normotensive pregnant women. Both groups of preeclamptic women showed decreased plasma levels of sCD163 and IL-10. Negative correlations between sCD163 and IL-1β (r = − 0.45; P = 0.014) and between sCD163 and TNF-α concentrations (r = − 0.54; P = 0.001) were observed in the severe PE group. The association between the pro-inflammatory cytokine profile and lower concentrations of sCD163 and IL-10 in plasma from women with severe PE suggests an impairment in the modulation of the systemic inflammatory response in this group of pregnant women with preeclampsia.
Keywords: CD163; Cytokines; Inflammation; Monocytes; Preeclampsia